Inlay retainers as bridge abutments in the posterior segment: Case report - Jevremović Danimir; Dodi Slobodan (Serbian Medical Society - Dental Section, Belgrade, 2007)
Inlay retained adhesive restorations are an interesting alternative to conventional methods when a single tooth is missing. The aim of this paper was to present possibilities for the application of inlay retained adhesive prosthodontic restorations based on composite systems. The clinical procedure is minimally invasive and simple to conduct. The introduction of fiber-reinforced composites as well as the improvement of adhesive cementing techniques makes these restorations a long-term solution with good esthetic and functional results. This case report offers an insight into the clinical procedure during the preparation of inlay retained adhesive restorations.